Biology concepts and connections - Liebaert, Richard; Mitchell; Reece (Redwood City, Calif. Benjamin/Cummings Pub. Co., 2000)
Interact with biology, perform experiments, run simulation, have fun and learn by completing the activities covering all of the biological concepts you study in class
System requirements: Windows 95/98/NT, 18 MB RAM, 18 MB free hard disk space, SVGA display, sound card, Netscape Navigator 4.0, Microsoft Internet Explorer 4.0 or higher, Netscape Communicator 4.5 (for windows) or higher
Keywords: Biology